SOCIO-ECONOMIC SECURITY MANAGEMENT – NEEDS, POSSIBILITIES AND APPLICATIONS - Popławski, Maciej (Management and Administration Journal, 2024)
This paper presents theoretical considerations on the needs and possibilities of socio-economic security management and practical application of the model of the system for diagnosing and forecasting socio-economic security in the region. The first part of the paper presents the validity and possibility of managing safety in relation to the definition of management and safety. In that context, the thesis was justified that the task of the state, as an organization, is to properly direct and dispose of the resources it has an influence over in order to ensure the highest possible level of security and eliminate its threats. The second part presents arguments for the need to create a tool for managing socio-economic security at the regional level. The importance of such a tool for making decisions regarding socio-economic policy and management practice at both the strategic and operational level was emphasized. Then, a multifactorial model of the system for diagnosing and forecasting socio-economic security of Polish regions was presented in terms of its contribution to the achievements of two scientific disciplines, and its practical application. Next, the possibilities and limitations in the construction of the model and its practical application as a management tool were presented.